Effect of different salt concentration on fermentation of stink bean (parkia speciosa) / Nurulhuda Muhamad - Muhamad, Nurulhuda (Faculty of Applied Sciences, 2017)
This project looks into the effect of addition of different salt level in fermentation of stink bean. In this study, fermented stink bean with 2%, 4%, and 6% salt, respectively, were analyzed in terms of lactic acid bacteria count, lactic acid content, and pH. The fermentation was carried out for 10 days at room temperature. Generally, lactic acid bacteria count shows a similar trend where initially there was increase in microbial count and then decrease afterwards. Fermented stink bean with 4% salt showed the highest lactic acid bacteria count followed by 2%, and 6% salt, respectively. For lactic acid content, fermented stink bean with 4% salt showed the highest lactic acid content, followed by fermented stink bean with 2%, and 6% salt, respectively. The final pH obtained in all fermented stink bean samples is 3.39 to 3.53. However, the statistical analysis shows no significant difference among fermented stink bean with 2, 4, and 6% of salt for all the attributes.